Differences in bread protein digestibility traced to wheat cultivar traits. (September 2022) - Lavoignat, Mélanie; Denis, Sylvain; Faye, Annie; Halupka, Laura; Perrochon, Sibille; Rhazi, Larbi; Giraudeau, Pascal; Déjean, Sébastien; Branlard, Gérard; Bancel, Emmanuelle; Ravel, Catherine
Abstract: Wheat grain storage proteins, i.e. the gluten proteins, and alpha-amylase trypsin inhibitors are partially resistant to gastrointestinal digestion. They figure among the wheat components that are potential triggers of non-celiac wheat sensitivity. To explore the digestibility of bread wheat proteins in relation to heritable plant traits, old and modern wheat varieties grown in two environments were genotyped, phenotyped, and processed into breads, which were partially digested in vitro in a system resembling human digestion. The extent of proteolysis measured after 2 h of digestion was variable. Digestion of proteins present in bread made from old wheat cultivars registered before 1960 and modern cultivars registered after 1960 was similar. No major plant trait was correlated to partial protein digestibility of bread from cultivars with high grain protein content. The protein digestibility of bread from high yield cultivars was influenced by protein composition, as well as the genetic distance per chromosome from a reference variety. Improving high yield cultivars by breeding for highly digestible proteins might help to mitigate adverse reactions to a range of wheat proteins in susceptible individuals. Graphical abstract: Image 1 Highlights: Breads made from distinct wheat flours are not digested at the same degree in vitro . Old and modern cultivars do not differ in bread in vitro protein digestibility. Plant traits of high yield cultivars are linked to partial protein digestibility.